PENGARUH PRESTASI BELAJAR MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 3 PEKANBARU - Yolani Safitri; Sri Kartikowati; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to know the effect of learning achievement of craft and entrepreneurship subjects on the interest in entrepreneurship. The Population in this study are the students of SMK Negeri 3 Pekanbaru with a total of 148 students and sample 109 people that was abtained using simple random sampling technique. Data collection technique using the questionnaires and documentation. Data was analyzed by simple linear reqresion technique support by SPSS version 21.The result showed that the learning achivements of craft and enterepreneurship subject. The results of the research showes that learning achievements of craft and entreprepreneurship subject has a significant positive effect on the intetrest in entrepreneurship of students this is evidenced from the learning achievements of craft and entrepreneurship subject, were categorized ‘good’ with 47 students (43%), were categorized ‘moderate’with 53 students (49%). While the total of its contribution is 83,9%. It was expected that. The remaining was influenced by other factors, like another subject except the craft and entrepreneurship subject.Key Words: Achievement, Subjects Craft, Entrepreneurship, Entrepreneurship Interest